‘Racial Profiling’ Revisited: The 1915 Indian Sepoy Mutiny in Singapore and the Impact of Profiling on Religious and Ethnic Minorities - Noor, Farish A. (Politics, religion & ideology, 2011)
The 1915 Singapore Indian Sepoy mutiny caught the British colonial authorities by surprise and led to significant damage to the environs of Singapore and the loss of lives. This article looks at the mutiny of 1915 and locates it in the broader context of related developments in other parts of the empire, and argues that it was an instance when ethnic and religious loyalties superseded loyalty to the empire. Though the mutiny was eventually put down and those responsible dealt with, it left the colonial authorities with the lingering problem of how to reconcile the political, ethnic and religious loyalties of colonial subjects who were in fact complex cosmopolitans, and whose own subjectivities were shaped by considerations other than those of the Empire. This remains a question that has to be addressed today, in a world where modern post-colonial states are likewise unable to deal with the multiple loyalties and identities of their own citizens.